Spleen and liver syndromes - Velazco V., Manuel (1957)
Being a synthesis effort and does not research, I must say, in summary, that the frequency of these syndromes is greater esplenohepáticos in our midst; that surely allow more precise tests nosological frame them within chapters specified, up to the demise of other ndrome itself. It is feasible, in the case of clinical pictures. common symptoms (bleeding, splenomegaly, hemocitopenia) with precise anatomical basis, initiated by neurovascular disorders with primary abnormality of the portal system and its special reactivity of the reticuloendothelial system. You can not talk about accuracy of spleen and liver injuries, as both bodies for their special histopathologic constitution, ill together. It is not known precisely, what are the ways that the spleen acts on bone marrow to determine disorders are considered as hypersplenism. Bleeding is frequent since the beginning of the disease and are almost always gastrorragias for phenomena already mentioned. At present, and at least in the initial stages of the disease, have two arms which by inhibiting alteration splenic, allows, if not the disappearance, of at least improvement of the disease. and they are splenectomy and the use of ACTH and cortisone. Who knows these facts, it is possible, in the future, consider the detailed mechanism of these conditions, similar to that determines the adaptation diseases.